Change in estrogen receptor, HER2, and Ki-67 status between primary breast cancer and ipsilateral breast cancer tumor recurrence. Issue 4 (April 2015) - Okumura, Y.; Nishimura, R.; Nakatsukasa, K.; Yoshida, A.; Masuda, N.; Tanabe, M.; Shien, T.; Tanaka, S.; Arima, N.; Komoike, Y.; Taguchi, T.; Iwase, T.; et al.
Abstract Introduction Changes in the biological marker status between primary and recurrent tumors are observed in breast cancer. However, their clinical significance is still uncertain, especially for patients with ipsilateral breast tumor recurrence (IBTR) after breast-conserving surgery. Patients and methods A total of 117 patients with IBTR without distant metastases were enrolled in this study. All patients were examined for estrogen receptor (ER), HER2, and Ki-67 in both the primary tumors and paired IBTR. We evaluated the impact of changes in these biomarkers between primary tumors and IBTR on the prognosis after IBTR. Results There were no associations of changes in the ER, HER2 status with distant disease-free survival (DDFS) after surgical resection of IBTR, whereas the change in the Ki-67 status between the primary tumors and IBTR was significantly correlated with DDFS (unadjusted: p = 0.0094; adjusted: p = 0.013). Patients in the "increased or remained high" Ki-67 group had a significantly shorter DDFS than those in the "decreased or remained low" Ki-67 group (5-year DDFS: 55.5 vs. 79.3%, respectively, p = 0.0084 by log-rank test). Conclusion An increased or persistently high Ki-67 status in the IBTR was significantly correlated with a poorer prognosis after IBTR.